Fundamentals of molecular virology - Acheson, N. H. (Wiley, 2007)
Designed for students learning about viruses for the first time(t the undergraduate or graduate level), Fundamentals of Molecular Virology is presented in a style which relates to today's students and professors. The text approaches learning about virology by presenting a set of chapters each of which covers a specific virus family, using one or two well-studied viruses as examples. Each chapter is designed to tell a story about the virus under discussion, and to portray the "personality" of that virus. The text incorporates lessons from classic and contemporary concepts providing a well-rounded presentation on the subject of virology. FEATURES OF FUNDAMENTALS OF MOLECULAR VIROLOGY Unique, Applied Chapter Stories. Each chapter presents a unique example or case to help introduce the students to the different viruses that will be studied or examined in that chapter. Evolutionary Boxes. Feature exciting and current developments in molecular virology. These are integrated throughout the entire book and can be found in every chapter. These help students understand the importance of currency and application of virology. The text contains a number of two-color figures which focus on the individual steps in virus replication and helps draw student's attention to important concepts and details. Coverage of Human Pathogens. Includes chapters that cover important human pathogens such as smallpox virus, measles virus, poliovirus, herpes viruses, human immunodeficiency virus, hepatitis B virus, Ebola virus, SARS corona virus, West Nile virus, and others. What instructors are saying about Fundamentals of Molecular Virology "I like the structured treatment that is presented in Acheson. Overall, it is one of the best written and clearly organized texts on the subject I have seen." - Jeannine Williams, College of Marin "I found the text very readable and believe it will appeal to a wide audience of students...I believe this text will have broad appeal in a field where few texts exist." - Michael Roner, The University of Texas at Arlington "The main strength of the book is the great molecular detail the author achieves, but still at a level that an undergraduate student should be able to master.